Anti-smoking themes: what works best for adolescents? - Farhangmehr, M.; Jalali, M.; Silva, C. L. (International Review on Public and Nonprofit Marketing, 2015)
Because of the heavy social and economic costs that it carries with it, smoking has become an important concern for a vast variety of stakeholders, from physicians to policy makers, among others. At the same time, however, there is the recognition that despite increasing restrictions, it is hard to compete with tobacco companies’ advertising and promotional budgets and efforts. Notwithstanding, there is some evidence that anti-smoking campaigns and advertisements can help mitigate the effects of such promotions and so contribute to reductions in smoking behaviours. In this sense, social marketing can have a fundamental role to play in promoting smoking cessation or helping avoid smoking adoption behaviours. Because most smokers adopt this behaviour at an early age, our interest in this paper lies on adolescent smoking behaviours, and in particular on how social marketing campaigns (through print advertisements, for instance) can help reduce smoking intentions. Against the backdrop of the Protection Motivation theory, the impact of different anti-smoking themes are tested for their impact on the perceived risks of smoking, adolescents’ ability to resist such behaviour, and their effect on smoking intentions. The results are promising, and provide important indications with regard to the types of themes which most impact adolescents